2017
DOI: 10.4314/ahs.v17i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Where there is no doctor: can volunteer community health workers in rural Uganda provide integrated community case management?

Abstract: Introduction: Integrated community case management (iCCM) involves assessment and treatment of common childhood illnesses by community health workers (CHWs). Evaluation of a new Ugandan iCCM program is needed. Objectives: The objectives of this study were to assess if iCCM by lay volunteer CHWs is feasible and if iCCM would increase proportions of children treated for fever, pneumonia, and diarrhoea in rural Uganda. Methods: This pre/post study used a quasi-experimental design and non-intervention comparison c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Task shifting has been successful in many other areas of health care delivery, including maternal health, integrated case management of childhood illnesses, and mental health. [47][48][49][50][51] Researches of a recent trial in India evaluated the effectiveness of a health promotion intervention in secondary schools. When delivered by lay counselors, there was strong evidence of impact; however, no effect was observed with teacher led delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Task shifting has been successful in many other areas of health care delivery, including maternal health, integrated case management of childhood illnesses, and mental health. [47][48][49][50][51] Researches of a recent trial in India evaluated the effectiveness of a health promotion intervention in secondary schools. When delivered by lay counselors, there was strong evidence of impact; however, no effect was observed with teacher led delivery.…”
Section: Discussionmentioning
confidence: 99%
“…This was the case in a study that promoted integrated service delivery for childhood diseases through volunteer health workers, therefore stimulating workforce expansion. 23 How to efficiently ensure motivation and create incentives for these workers remains open to investigation, but lessons can be learned from similar efforts. 24 , 25 Interestingly, a multi-country study on community-led interventions reported non-financial incentives as being more effective in motivating community volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…As presented in Figure 1, nine parishes in Kyabugimbi sub-county were selected as sites for advanced CHW training in iCCM as per the protocol of a controlled intervention trial 35 building on previous studies of CHW engagement in iCCM. [32][33][34] The choice of sites was based on the burden of childhood illness in this sub-county and on difficulty of access to the nearest level IV health centre.…”
Section: Methodsmentioning
confidence: 99%
“…The centres include ward beds, an operating theatre, laboratory and blood transfusion facilities. 36 In 98 villages participating in the background trial, 35 selected CHWs (n=196) received 5-day basic training followed by additional iCCM preparation. Training in iCCM focused on skills and knowledge needed to assess, treat and, if necessary, refer to a higher level of care, young children with fever, presumed pneumonia or diarrhoea.…”
Section: Methodsmentioning
confidence: 99%